Single-molecule nanopore enzymology - Willems, Kherim (Philos Trans R Soc Lond B Biol Sci, 2017)
Biological nanopores are a class of membrane proteins that open nanoscale water conduits in biological membranes. When they are reconstituted in artificial membranes and a bias voltage is applied across the membrane, the ionic current passing through individual nanopores can be used to monitor chemical reactions, to recognize individual molecules and, of most interest, to sequence DNA. In addition, a more recent nanopore application is the analysis of single proteins and enzymes. Monitoring enzymatic reactions with nanopores, i.e. nanopore enzymology, has the unique advantage that it allows long-timescale observations of native proteins at the single-molecule level. Here, we describe the approaches and challenges in nanopore enzymology. This article is part of the themed issue ‘Membrane pores: from structure and assembly, to medicine and technology’.